2011
DOI: 10.1269/jrr.10068
|View full text |Cite
|
Sign up to set email alerts
|

Size, Concentration and Incubation Time Dependence of Gold Nanoparticle Uptake into Pancreas Cancer Cells and its Future Application to X-ray Drug Delivery System

Abstract: One of the restrictions in the potential use of gold markers for medical imaging/tracking of harder tumors is its size. We propose to use gold nanoparticles which, due to its small size, can be administered conveniently via intravenous injection. One of the factors that determine the clinical utility of nanoparticles is the ability to enter cells. In this report, the stability of gold nanoparticles mixed with different media was determined by UV-vis spectroscopy. Gold nanoparticle size was confirmed by TEM. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 16 publications
5
50
0
1
Order By: Relevance
“…Some studies have reported saturation of nanoparticle uptake within hours [11], whereas others after several days [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported saturation of nanoparticle uptake within hours [11], whereas others after several days [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nanoparticles are also reported to demonstrate a size effect on endocytosis; bare gold nanoparticles with 20-50 nm in diameter have demonstrated that the most efficient cellular uptake between 10 and 100 nm size ranges in cultured cancer cells because gold nanoparticles with these size ranges may balance between the elevated elastic energy associated with increased curvature of the cell membrane and reduced entropy associated with receptor/ligand immobilization [75][76][77]. Surface chemistries of delivery vehicles are apparently more critical for their endocytosis, compared to size and shape.…”
Section: Design Criteria To Overcome Intracellular Barriersmentioning
confidence: 99%
“…The significant reduction of cellular viability at zero time point and the following 60 min as well the significant loss of cellular integrity under the microscope may support this assumption. Moreover, as nanoparticles internalization and accumulation inside the cells depend primarily on the incubation time with nanoparticles as stated by Trono et al [26], the significant reduction of viability in cells exposed to AgNSs up to 10 minutes (63.3%) is likely due to possible action of silver nanoparticles and produced ions on the outer cellular membrane of RAW cells and not because of the possible AgNPs inside cells in this short term periods. This scenario supported by Beer et al [27] who returned the toxic effect of AgNPs to the released ion mainly than cellular internalization.…”
Section: Discussionmentioning
confidence: 80%